METHODOLOGICAL FEATURES OF FORMATION OF PEDAGOGICAL TOLERANCE OF FUTURE VOCATIONAL TEACHERS BY MEANS OF INTERDISCIPLINARY INTEGRATION - DIDUR, Andrii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The main goal of the modern educational system is seen as the development of a multifaceted personality, aware of the depth of relationships between objects of reality and various concepts, based on developed critical thinking and aesthetic culture. Among the main goals of professional pedagogical education, a significant role is given to the formation of pedagogical tolerance, which, in addition to the formation of basic skills, involves mastering competencies in recognizing the value and demonstrating respect for intersubject differentiation, refusing coercion and the desire to change the environment according to one's own model. The purpose of the article is to analyze the methodological features of the formation of pedagogical tolerance of future teachers of professional education by means of interdisciplinary integration. The article considers the concept of the formation of interdisciplinary connections, which has the functionality of an integrated approach to the development of pedagogical tolerance. It is established that the studied process requires the formation of a stable skill of adequate mutual understanding in students, the desire to democratize relations with participants in the professional communication process. It is emphasized that interdisciplinary integration projects are important educational tools of the pedagogical strategy for the formation of life skills, including tolerance and professional ethics. It is substantiated that the modern educational space requires teachers to pay special attention to the concept of a culture of tolerance, to find ways to develop it, and to develop and adapt innovative technologies and methods. It has been proven that the effective use of the potential of integrated classes contributes to the optimization of cognitive activity, the advancement of critical thinking and the sustainable development of an aesthetic worldview, which in synergy ensures the successful formation of pedagogical tolerance in the process of obtaining professional pedagogical education.